Does the Protection of Minority Groups in Xinjiang Fail? - Gunawan, Yordan (Faculty of Law, Sriwijaya University, Indonesia, 2020)
Nowadays, many human rights violations related to religion, race or culture exist. In 2018, The Council on Foreign Relations (CFR) estimated around two million Uyghur were arrested by the Chinese government without due process of law and forced to accept the political doctrine of the Chinese Communist Party. These actions include physical torture and restrictions on religious freedom. Article 2 of 1948 UDHR stipulates the prohibition of discrimination against race, colour, sex, language, religion, political or other opinions, national or social origin, property, birth, or another status. The paper aims to analyse human rights violations against the Uyghur and legal efforts to protect freedom of human rights for Uyghur in China. Human Rights have been fully regulated by the 1948 Universal Declaration of Human Rights (UDHR). By using statutory and case approach, the result shows that the actions taken by the Chinese government have violated legal provisions including the Declaration and the International Convention on the Elimination of All Forms of Racial Discrimination (ICERD) and the International Covenant on Economic, Social and Cultural Rights (ICESCR). The government of China is also failing to uphold its responsibility to protect.